The Perception of ―A Smart City In Terms of Cognitive Interpretation on the Example of the Notion and Image of ―A Smart City among Students (Future Architects) (International Journal of Psychosocial Rehabilitation, 2020)
Scenarios for the future of cities largely depend on technologies developed in the field of architecture and perception and understanding of the problem of improving cities by students - future architects. The article is devoted to the actual linguistic problem of perceiving the image of “a smart city” by students (future architects). The image of “a smart city” is classified by linguists as an elusive image that is weakly categorized. The purpose of this article is a systematization and linguistically cognitive analysis of lexical units verbalizing the image of “a smart city” by students (future architects). That allows us to draw conclusions about the peculiarities of future architects interpreting the “smart city” as an object of reality and to identify the structure and cognitive sources of the language description of the image of “smart citie"s. For a systematic description of the interpretation of the image of “a smart city” by students - future architects—the concept of image interpretation developed by the Russian linguist S.V. Draft. The study was carried out using linguistic methods and methods of cognitive linguistics. The structure of the meaning of lexical units and their functioning in the context, in conjunction with extra-linguistic factors, was taken into account. The method of image description adopted in the works of Russian linguists and cognitive scientists was used. The experimental conclusions presented in this article are of interest to linguists and cognitologists who deal with the problems of linguistic understanding of the semantics of the "elusive" and the perception of various types of texts-projects and architectural objects of the urban environment—by young people.